The Problem of Implementing Self Declared Halal Certification for Micro and Small Enterprises - Hasan, Maisyarah Rahmi; Jailani, Munawar Rizki (Institut Agama Islam Negeri Lhokseumawe, 2024)
The mandatory introduction of 2024 halal certification encourages the government to expedite the approval of halal certifications. Several programmes are being launched to accelerate the realization of halal certification in Indonesia, one of them is the Free Halal Certification (SEHATI) program, which has been launched since 2022 with free halal Certification facilities targeting small enterprises with the Self Declare halal certificate submission scheme. The study aims to examine the problems faced by the organizers of the halal product guarantee and the perpetrators of the UMK in implementing the free halal certification (SEHATI) self-declaration path. The type of research used is empirical research with a qualitative descriptive approach. The results of this study show that the application of halal self declaration certification has begun to be applied since 2022, as much as 1 million kouta halal self declare certification is given to UMK perpetrators with product criteria that have been established on the basis of competition number 33 year 2023 on the jurisprudence of self declaring certification filing criteria. With its implementation, there are still obstacles and difficulties in its application, both that originate from the organizers namely BPJPH, as well as with LP3H, PPH accompanying, and also UMK perpetrators. Among the internal factors faced are related to the requirements to be met by UMK persons, the application procedure that is all-digitalized, and the problems faced after the legal certificate is issued.